Disguised Disciplinary Sanctions For A Public Official - Ahmed Smail Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The public job is very important, and the public employee is not less than this high degree of prestige, and therefore his relationship with the state must be organized according to legal foundations and rules so as to ensure him a good performance and achieve the public interest of the community, from the beginning of the appointment of the public employee and the conditions and method of this appointment Through the ways the employee performs his work duties, in a manner that guarantees the proper management of its public facilities on the one hand, and the employee has the necessary guarantees regarding what may be taken against him on the other hand, and ends with the termination of his job relationship with the state, and the breach of the public employee's job duties would Breach of moral The general state systematically and continuously, which represents the general objectives and basic norms of administrative law; so keen administrative legislator in the comparison of legislation on the order of certain sanctions signed by the public employee, who upset her duties. The disciplinary system has several elements, namely, the disciplinary or disciplinary crime, the disciplinary penalty and the disciplinary authority, and the goal is to hold the employee accountable if he breaches his job duties in maintaining the functioning of the state's public facility, and not to tamper with what is inconsistent with that, and then there is a link between disciplining the public employee And between committing a disciplinary crime, if the commission of any crime entails the fulfillment of his legal responsibility, whether this responsibility is civil, criminal, or disciplinary. A disciplinary crime is everything that an employee commits and that would violate job duties or violate administrative laws and regulations, as the disciplinary authority gave itself the right to inflict a penalty, without taking into account the procedural and substantive guarantees established for the benefit of the public employee, and then it was necessary to articulate rights and duties Public employee. The administrative apparatus is one of the largest state agencies, due to the presence of a large number of employees working in the running of state facilities, which is not without the excesses of the administrative authorities, so it was necessary to address these abuses - the necessity of the administrative authority's commitment to respect the rights of the public employee, so that the system does not transform Tunable to a painful whip of the public employee, as some administrative measures may be taken that will affect the legal position of the public employee, which is known as the codified penalties under discussion. Consequently, the disciplinary system is based on a set of general rules, which appear clear in the context of the relationship between the public employee and the facility or the administration in which he works, through the so-called disciplinary authority, which is the authority that the presidential authorities, disciplinary boards or disciplinary courts begin and these procedures begin From the start of assigning the violation works to the public employee, through moving the disciplinary lawsuit against the employee, and ending with the issuance of the disciplinary ruling, it is executed. Finally, the judicial system is the one that undertakes the task of determining the state, qualitative, or value jurisdiction of each court, particularly in the countries that adopt the dual judicial system, that is, it takes the necessity of having two judicial bodies, the first of which is the ordinary judiciary, and it is the one who is assigned the task of examining disputes. The list between ordinary individuals and the second is the administrative judiciary, which is assigned to it the task of examining administrative disputes.